1991
DOI: 10.1111/j.1365-2648.1991.tb03428.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsibility and autonomous nursing practice

Abstract: In this paper, the consequences were there greater autonomy in nursing practice, are considered. Autonomous practice implies accountability which entails both personal and professional responsibility: a personal responsibility to endorse ethical conduct consistent with professional practice; and a professional responsibility to exercise discretionary powers to the ultimate benefit of the patient. In this context, discretionary responsibility implies: recognizing a patient's wants may not be consistent with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Despite efforts to promote the independent contribution of nursing (Finn 2001; Hayes et al . 2010; Holden 1991; Willis 1993), it appears that throughout the Bachelor of Nursing program students continue to graduate believing that work in areas associated with the manipulation of technology is high status and rewarding nursing. Indeed, Table 1 can almost be divided into two halves.…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to promote the independent contribution of nursing (Finn 2001; Hayes et al . 2010; Holden 1991; Willis 1993), it appears that throughout the Bachelor of Nursing program students continue to graduate believing that work in areas associated with the manipulation of technology is high status and rewarding nursing. Indeed, Table 1 can almost be divided into two halves.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MacKinnon, McIntyre and Quance (2005), who explored the meaning of nurse's presence during childbirth, found that women particularly valued ‘the way in which a nurse was “there” for them’ during childbirth (28). This sense of nurse advocacy is widely addressed in the literature (see Holden 1991; Mallik 1997; Hewitt 2002). Similarly, Parratt and Fahy (2004) found that a ‘holistically safe’ birthing place was jointly constructed by midwife and women and also that the midwife's presence positively contributed to the birth setting (11) in terms of being the woman's advocate.…”
Section: Place As It Appears In Nursingmentioning
confidence: 99%
“…Autonomous decision making does not involve the exercise of routine tasks or the unquestioning enactment of physician orders ( Coser 1991, Holden 1991, Kramer & Schmalenberg 1993). Instead, self‐direction and intellectual flexibility are required to negotiate and compromise.…”
Section: Descriptions Of the Conceptmentioning
confidence: 99%
“…Instead, self‐direction and intellectual flexibility are required to negotiate and compromise. Discretionary decision making is crucial to autonomous practice ( Batey & Lewis 1982, Benner 1984, Holden 1991). Competent nurses exercise discretionary decision making by using the critical conscience to select a course of action consistent with the client’s needs.…”
Section: Descriptions Of the Conceptmentioning
confidence: 99%